THE CONCEPT OF SOCIAL EDUCATION ACCORDING TO JOSÉ ORTEGA Y GASSET AND ITS CONTEMPORARY REFERENCES - Kharkhula Yaroslav (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article is dedicated to the figure of Jose Ortega y Gasset, a twentieth-century thinker who founded a new school of philosophy and gathered many students around him. The Spanish thinker made teaching and pedagogy his profession and vocation. As a result, Jose Ortega y Gasset was able to gain fame as a «citizen educator» or «political educator». The aim of this article is to analyze the pedagogical aspects of José Ortega y Gasset's social theory. The philosophical assumptions of this author, his concept of global reality, largely define his pedagogy. Ortega y Gasset's philosophy is a philosophy that focuses more than on metaphysics on the problems of social circumstances. The author focuses on the main areas of his research, which define the thinker as a representative of liberalism with a clear social character. However, his concept of the elite was often interpreted as elitist, close to conservative attitudes, which was the result of too simplistic interpretation of the concepts of «mass» and «elite» in the reasoning of the Spanish philosopher. The article begins with an analysis of selected aspects of Ortega y Gasset's biography, paying particular attention to pedagogical references in order to better show the evolution of his views and to better understand to what extent different situations of «everyday life» influenced the concepts created by the author. This analysis of his biography focuses on the period whose cut-off date is 1914. After this contextualization, the assumptions of the concepts developed by the Spanish thinker in this phase of his work will be analyzed, emphasizing the pedagogical elements present in it. This stage of the Spanish thinker's philosophy is often referred to in the literature as the period of «social pedagogy».